KONSEP TRANSFORMASI SPASIAL KORIDOR KAMPUNG KAUMAN SEMARANG: INTEGRASI IDENTITAS BUDAYA DAN RELIGI DALAM ARSITEKTUR TRADISIONAL - Sepli Yandri; Yessy Christanti Silaban; Rusydina Sabila Fauzi (Smart Education, 2026)
This study aims to formulate a preservation strategy for Kauman Village in Semarang as a sustainable cultural and religious tourism destination through contextual corridor design. As an embryo of urban growth, Kauman currently faces physical degradation and identity erosion driven by uncontrolled modernization. The research methodology adopts Roger Trancik's integrated urban design theory, incorporating figure/ground (mass and void), linkage (visual-structural connectivity), and place (socio-cultural meaning of space) analyses, which are further synthesized through a SWOT matrix. The results formulate the